The CentriMag Centrifugal Blood Pump as a Benchmark for In Vitro Testing of Hemocompatibility in Implantable Ventricular Assist Devices. Issue 2 (28th July 2014) - Chan, Chris H.H.; Pieper, Ina Laura; Hambly, Rebecca; Radley, Gemma; Jones, Alyssa; Friedmann, Yasmin; Hawkins, Karl M.; Westaby, Stephen; Foster, Graham; Thornton, Catherine A.
Abstract Implantable ventricular assist devices (VADs) have proven efficient in advanced heart failure patients as a bridge‐to‐transplant or destination therapy. However, VAD usage often leads to infection, bleeding, and thrombosis, side effects attributable to the damage to blood cells and plasma proteins. Measuring hemolysis alone does not provide sufficient information to understand total blood damage, and research exploring the impact of currently available pumps on a wider range of blood cell types and plasma proteins such as von Willebrand factor (vWF) is required to further our understanding of safer pump design. The extracorporeal CentriMag (Thoratec Corporation, Pleasanton, CA, USA) has a hemolysis profile within published standards of normalized index of hemolysis levels of less than 0.01 g/100 L at 100 mm Hg but the effect on leukocytes, vWF multimers, and platelets is unknown. Here, the CentriMag was tested using bovine blood (n = 15) under constant hemodynamic conditions in comparison with a static control for total blood cell counts, hemolysis, leukocyte death, vWF multimers, microparticles, platelet activation, and apoptosis. The CentriMag decreased the levels of healthy leukocytes (P < 0.006), induced leukocyte microparticles (P < 10−5), and the level of high molecular weight of vWF multimers was significantly reduced in the CentriMag (P < 10−5) all compared with the static treatment after 6 h in vitro testing. Despite the leukocyte damage, microparticle formation, and cleavage of vWF multimers, these results show that the CentriMag is a hemocompatible pump which could be used as a standard in blood damage assays to inform the design of new implantable blood pumps.